Neurobehavioral phenotype of Kabuki syndrome: Anxiety is a common feature - Kalinousky, Allison J.; Rapp, Tyler; Hijazi, Hadia; Johnson, Jennifer; Bjornsson, Hans Tomas; Harris, Jacqueline R. (Frontiers in Genetics, 2022)
Kabuki syndrome (KS) is a Mendelian Disorder of the Epigenetic Machinery (MDEM) caused by loss of function variants in either of two genes involved in the regulation of histone methylation, KMT2D (34-76%) or KDM6A (9-13%). Previously, representative neurobehavioral deficits of KS were recapitulated in a mouse model, emphasizing the role of KMT2D in brain development, specifically in ongoing hippocampal neurogenesis in the granule cell layer of the dentate gyrus. Interestingly, anxiety, a phenotype that has a known association with decreased hippocampal neurogenesis, has been anecdotally reported in individuals with KS. In this study, anxiety and behavior were assessed in a cohort of 60 individuals with molecularly confirmed KS and 25 unaffected biological siblings, via questionnaires (SCARED/GAS-ID and CBCL/ABCL). Participant age ranged from 4 to 43 years old, with 88.3% of participants having a pathogenic variant in KMT2D, and the rest having variants in KDM6A. In addition, data was collected on adaptive function and positive affect/quality of life in participants with KS using appropriate online surveys including ABAS-III and PROMIS Positive Affect. Survey scores were compared within the KS participants across age groups and between KS participants and their unaffected siblings. We found that children with KS have significantly higher anxiety scores and total behavior problem scores than their unaffected siblings (p=0.0225, p<0.0001). Moreover, a large proportion of affected individuals (22.2% of children and 60.0% of adults) surpassed the established threshold for anxiety; this may even be an underestimate given many patients are already treated for anxiety. In this sample, anxiety levels did not correlate with level of cognitive or adaptive function in any KS participants, but negatively correlated with positive affect in children with KS (p=0.0005). These findings indicate that anxiety is a common neurobehavioral feature of KS. Providers should therefore carefully screen individuals with KS for anxiety as well as other behavioral issues in order to allow for prompt intervention. Neurobehavioral anxiety measures may also prove to be important outcome measures for clinical trials in KS.